Challenging anxious cognitions or accepting them? Exploring the efficacy of the cognitive elements of cognitive behaviour therapy and acceptance and commitment therapy in the reduction of children's fear of the dark. (28th January 2019) - Simon, Ellin; Driessen, Sabine; Lambert, Ann; Muris, Peter
Abstract : Anxiety is highly prevalent in pre‐adolescent children. Distorted cognitions are characteristic for dysfunctional levels of anxiety. However, applying cognitive elements in pre‐adolescent children cannot be fully ascertained, as it is not until adolescence before children can apply logical and abstract reasoning in a sophisticated manner. Cognitive behaviour therapy (CBT) and acceptance and commitment therapy (ACT) both target distorted cognitions. Whereas CBT encourages children to change the content of negative cognitions by applying cognitive restructuring, ACT stimulates youth to have a more accepting attitude towards these thoughts by applying cognitive defusion. The current study examined the efficacy of applying cognitive elements and compared the cognitive elements of CBT and ACT in pre‐adolescent children. We included no behavioural elements to specifically study the developmental appropriateness of the cognitive elements in this age group. Highly anxious children, aged 8–12 years were randomised to a 30‐minute cognitive restructuring ( n  = 21) or cognitive defusion intervention ( n  = 22). Subjective fear of the dark levels, behavioural darkness toleration, and comprehension and fun associated with the interventions were assessed. Both interventions had a significantly positive impact on children's fear of the dark. Cognitive restructuring led to more favourable results on subjective fear than cognitive defusion, no differences were found for darkness toleration.